2017
DOI: 10.1155/2017/2084621
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence Study of Mesa-Type InGaAs/InAlAs Avalanche Photodiode Characteristics

Abstract: Avalanche photodiodes (APDs) are key optical receivers due to their performance advantages of high speed, high sensitivity, and low noise. The most critical device parameters of APD include the avalanche breakdown voltage and dark current. In this work, we study the temperature dependence of the breakdown voltage and dark current of the mesa-type APD over a wide temperature range of 20–145°C. We institute an empirical model based on impact ionization processes to account for the experimental data. It is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…Assuming half of the voltage drop is across the multiplication layer, we can estimate the breakdown electric field at the multiplication layer (Saleh et al, 2001). Our previous study showed that the breakdown fields in the multiplication layers for 2.5G, 10G, and 25G APDs were about 560, 800, and 1300kV/cm, respectively (Huang et al, 2017). Since the breakdown electric field is the maximum at the multiplication layer, we expect that this layer may become the weak spot when exposing to the harsh environmental stresses.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming half of the voltage drop is across the multiplication layer, we can estimate the breakdown electric field at the multiplication layer (Saleh et al, 2001). Our previous study showed that the breakdown fields in the multiplication layers for 2.5G, 10G, and 25G APDs were about 560, 800, and 1300kV/cm, respectively (Huang et al, 2017). Since the breakdown electric field is the maximum at the multiplication layer, we expect that this layer may become the weak spot when exposing to the harsh environmental stresses.…”
Section: Methodsmentioning
confidence: 99%
“…Among the various layers of APD, the charge control layer is denoted as the minimum feature size. Semiconductor photodetectors have evolved from 2.5G APD to 10G APD and recently advanced to 25G APD [22,23]. Driven by 100G datacenter demand, the development and manufacturing of 25G APD have been accelerated with rapid pace and growth [24][25][26].…”
Section: Nanoscale Photonic and Electronic Devicesmentioning
confidence: 99%
“…For 10G APD, mesa-type structure with coplanar p-and n-metal contacts is employed to enhance the speed [23,36]. The active region is sandwiched between the P-mesa at the top and the N-mesa at the bottom.…”
Section: Nanoscale Iii-v Semiconductor Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kleinov et al have paid to the charge layer in order to optimize the InAlAs/InGaAs structure for low band discontinuities and an appropriate electric field distribution for the gains less than 300 [10]. Recently, Huang et al [11] have studied temperature dependency of InGaAs based multiplication region APDs.…”
Section: Introductionmentioning
confidence: 99%